Comparison of drug survival and clinical outcome in patients with ankylosing spondylitis treated with etanercept or adalimumab. (4th March 2018) - Ruwaard, J; l'Ami, MJ; Marsman, AF; Kneepkens, EL; van Denderen, JC; van der Horst-Bruinsma, IE; Nurmohamed, MT; Wolbink, G
Abstract : Objective : To compare rates of drug survival and clinical response during 2 years of follow-up in ankylosing spondylitis (AS) patients treated with etanercept or adalimumab in routine care. Method : Biological-naïve consecutive AS patients treated with etanercept (n = 163) or adalimumab (n = 82) were followed. Treatment discontinuation was due to inefficacy, adverse events, loss to follow-up, planning a pregnancy, or uveitis. Disease activity was assessed by the Ankylosing Spondylitis Disease Activity Score using C-reactive protein (ASDAS-CRP). Moderate disease activity was defined as an ASDAS-CRP < 2.1. Results : Twenty-seven patients (32.9%) treated with adalimumab and 30 (18.4%) with etanercept discontinued treatment. Cox regression analysis demonstrated a significant difference in survival rate between discontinuation of the drug in adalimumab patients compared with etanercept patients [hazard ratio (HR) 2.1, 95% confidence interval (CI) 1.3–4.5, p = 0.005; corrected for confounding factors: HR 2.5, 95% CI 1.3–4.5, p = 0.006]. There was no significant difference at 2 years of follow-up between the adalimumab- and the etanercept-treated patients in mean ± sd ASDAS-CRP (1.9 ± 1.1 and 2.0 ± 0.9, respectively, p = 0.624), and 23 out of 34 (67.6%) compared to 71 out of 117 (60.7%) reached ASDAS-CRP moderate disease activity (odds ratio 0.738, 95% CI 0.329–1.657, p = 0.530). Conclusion : No significant difference was found between AS patients treated with etanercept and those treated with adalimumab in mean ASDAS-CRP and reaching ASDAS-CRP minimal disease activity at 2 year follow-up. Drug survival rate was higher in etanercept- compared to adalimumab-treated patients. However, this should be interpreted cautiously as the risk of allocation bias cannot be excluded.